Physical Exercise for the Treatment of Neuropsychiatric Disturbances in Alzheimer’s Dementia: Possible Mechanisms, Current Evidence and Future Directions - Matura, Silke; F. Carvalho, André; S. Alves, Gilberto; Pantel, Johannes (Current Alzheimer Research, 2016)
Behavioral and psychological symptoms of dementia (BPSD), also known as neuropsychiatric or non-cognitive symptoms are common and often distressing features of Alzheimer's Dementia. BPSD significantly increase patient suffering, early institutionalization and caregiver's burden. The clinical management of BPSD is dominated by a pharmacological approach, although these medications often come with serious adverse side-effects. There are only few nonpharmacological treatment strategies for BPSD. A substantial amount of intervention studies that have investigated non-pharmacological treatment options for BPSD have focused on physical exercise. Although these studies are very heterogeneous in terms of type and severity of dementia, as well as type and duration of the exercise intervention, the overall picture shows a positive effect of physical exercise in alleviating BPSD. There is evidence that numerous mechanisms contribute to the positive effect of physical exercise on BPSD. No attempt has been undertaken so far to give an overview of the existing knowledge regarding these mechanisms. Therefore, the current review aims to integrate the existing evidence on psychological and neurobiological mechanisms that contribute to the beneficial effects of physical exercise in ameliorating BPSD in Alzheimer's dementia. A discussion of psychological mechanisms such as improved sleep and stress reduction will be followed by a discussion of neurobiological mechanisms including the exercise induced change in neurotransmitter concentrations, increased synthesis of neurotrophins and immune activation. The review closes with recommendations for future research to overcome the shortcomings of existing studies and broaden the current knowledge on the positive effects of physical exercise on BPSD.
Keywords: psychological mechanisms